PERUBAHAN STRUKTUR GERAKAN PERLAWANAN PETANI RENGAS - Mohammad Syawaludin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2016)
Research study focuses on changes in the structure of the movement and its relation to the achievement of objectives of the struggle. Form of peasant movement Rengas  to structure the resistance movement and the movement to change the structure in accordance with the environmental conditions encountered resistance.  Through the analysis of periodic this research can parse the initial formation process of the development of the structure and expansion of the structure of the movement until the action changes the structure of the movement after he did a mass reklaiming. Methods of qualitative research approaches used for the case study approach, this type of approach was chosen because the more stressed the rationalism and the reality of the social, political, cultural. In addition the election method of the single case study is a research strategy that will help researchers investigate carefully a program, event, activity, process or a group of individuals. Cases where limited by time and the type of activities which the researchers were able to gather information in a complete and scalable.